Implementing an Integrated Management System (IMS) to Optimize Procurement and Supplier Development Processes in a Manufacturing Company: A Case Study - Malik, Mubasher Ali Moazzam (My University, 2024)
The adoption of Integrated Management Systems (IMS) in manufacturing is growing. However, empirical research on integrating procurement and supplier development processes within IMS frameworks remains limited, particularly in manufacturing contexts. This study addressed this gap by investigating IMS implementation in a manufacturing company’s procurement and supply development operation, focusing specifically on the absence of frameworks aligning these functions with ISO standards and Sarbanes-Oxley (SOX) compliance requirements. The research aimed to develop and validate an IMS framework that optimizes procurement and supplier development processes while maintaining regulatory compliance. A single case study approach utilizing mixed methods combined qualitative data from questionnaires (n=7) and document analysis with quantitative assessments through structured survey (n=33). Business Process Reengineering methodologies (BPR) and Business Process Model and Notation (BPMN) were applied to redesign workflows, integrating category management, strategic sourcing, operational purchasing, and supplier development functions. The implementation resulted in significant improvements across key performance metrics: process clarity (78-94%), compliance adherence (71-88%), and stakeholder satisfaction (84-94%). The redesigned processes demonstrated effectiveness in supplier audits (94% satisfaction) and RFx processes (92% satisfaction). The study's primary contributions include an empirically validated IMS implementation framework, a practical methodology for BPMN application in process optimization, and a systematic approach for aligning procurement processes with international compliance requirements. The research was limited by its single case focus, short-term implementation assessment, and exclusion of new software system implementations. Future research should examine long-term implementation effects across different organizational contexts, explore cross-industry applications, and investigate the integration of emerging technologies like artificial intelligence and blockchain within IMS frameworks. These findings provide valuable insights for manufacturing organizations seeking to optimize their procurement and supplier development processes while maintaining international compliance standards.
Keywords: supply chains; processes; process management; suppliers; purchases; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics